The post-American world - Zakaria, Fareed; Camden conference 2009. (New York : Simon & Schuster Audio, 2008)
The author of the bestselling "The Future of Freedom" describes a world in which the U.S. will no longer dominate the global economy. He sees the "rise of the rest" as the great story of our time, and one that will reshape the world.
Unabridged.
Compact discs.
Read by the author.
Keywords: Twenty-first century -- Forecasts; International relations -- Forecasting; International economic relations -- Forecasting; World politics -- 21st century -- Forecasting; East and West; Globalization -- Forecasting; United States -- Foreign relations -- 21st century -- Forecasting; Audiobooks